2008
DOI: 10.1111/j.1742-6723.2008.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of streaming in a regional emergency department

Abstract: The implementation of the streaming model had an impact on the two performance indicators associated with length of stay in this regional ED, but did not have a significant impact (positive or negative) on the percentage of patients who did not wait to be seen. These results might interest other EDs in regional hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…We see an identical streaming methodology in Kinsman et al (2008), resulting in continual reduction in LOS times for both patient types. Inspired by the work of King et al (2006), Kelly et al (2007) segregates patient flow.…”
Section: Patient Streamingmentioning
confidence: 88%
See 1 more Smart Citation
“…We see an identical streaming methodology in Kinsman et al (2008), resulting in continual reduction in LOS times for both patient types. Inspired by the work of King et al (2006), Kelly et al (2007) segregates patient flow.…”
Section: Patient Streamingmentioning
confidence: 88%
“…Acuitybased triage, a wide source of publication in the nontechnical arena, has not seen abundant focus in OR/OM (with only a few exceptions such as Konrad et al, 2013). We look for more prominent use upcoming in the area of triage, especially with the recent successful innovations reported in both OR/OM and Emergency Medicine literatures in areas such as complexity-based triage (Saghafian et al, 2014), disposition-based triage and patient streaming (King et al, 2006;Kelly et al, 2007;Kinsman et al, 2008;Saghafian et al, 2012), and telemedicine-based triage (Traub et al, 2013).…”
Section: Concluding Remarks and Research Prospectsmentioning
confidence: 98%
“…It was suggested that timeliness is an important factor of patient satisfaction for non-urgent care based on the research of an ED fast track operation [35]. The research also found different results of LOS for different patients in assessing the impact of streaming used in an ED [13]. The implication of triage teams to achieve the overall impact on patient LOS may depend on each ED's unique characteristics [29].…”
Section: Fast Track Treatment (Ftt)mentioning
confidence: 96%
“…A decision tool to determine the application and limitations is required to examine these preliminary findings [10,13]. This research evaluates the fast track treatment (FTT) strategy proposed to reduce the waiting time at a hospital ED using agent-based simulation modeling.…”
Section: Introductionmentioning
confidence: 99%
“…The first project led to a forecasting model for predicting demand for ED services (Champion et al, 2007). The second project was concerned with evaluating a fast-track approach to managing patient flow in the ED at BH (Kinsman et al, 2008).…”
Section: Introductionmentioning
confidence: 99%